Eating speed and the risk of type 2 diabetes: explorations based on real-world evidence - Sai Krishna Gudi (Korean Society of Pediatric Endocrinology, 2020)
Metabolic syndrome, especially diabetes, has gained global attention over the past few decades and became one of the major public health concerns. Alongside known and well-established risk factors, eating behaviors, mainly eating speed has shown the potential as one of the novel risk factors that could supplement the development of diabetes. However, there is a paucity in evidence, and only a few studies have addressed this question so far. In this review, with a focus on eating speed and the risk of developing diabetes, authors attempted to shed some light on the high-quality studies that were conducted around the world using real-world data in drawing inferences, which could add-on to the literature and assist public in making informed decisions.